2000
DOI: 10.1038/emm.2000.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term ethanol on the proliferative response of Swiss 3T3 cells to mitogenic growth factors

Abstract: Both adaptive and deleterious responses of cells to ethanol are likely triggered by short-term interactions of the cells with ethanol. Many studies have demonstrated the direct effect of ethanol on growth factor-stimulated cell proliferation. Using Swiss 3T3 cells whose growth was inhibited by ethanol in a concentration-dependent manner, we further investigated the molecular mechanisms of acute ethanol treatment by examining its effect on EGF-and PDGF-mediated cellular signaling systems for the mitogenic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Epidemiological studies highlighted that heavy alcohol drinking promotes colon cancer progression [44], although the underlying molecular mechanisms are still not clear. Data reported in this paper show that colon cancer cells survive even under treatment with high doses of ethanol (100–300 mM), which have been shown to exert toxic effects in other tumor cell lines [45,46]. It is interesting to note that concentrations ranging from 10 to 100 mM correspond to blood levels in humans that could result from moderate-to-heavy alcohol drinking [47].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies highlighted that heavy alcohol drinking promotes colon cancer progression [44], although the underlying molecular mechanisms are still not clear. Data reported in this paper show that colon cancer cells survive even under treatment with high doses of ethanol (100–300 mM), which have been shown to exert toxic effects in other tumor cell lines [45,46]. It is interesting to note that concentrations ranging from 10 to 100 mM correspond to blood levels in humans that could result from moderate-to-heavy alcohol drinking [47].…”
Section: Discussionmentioning
confidence: 99%
“…EGF can modulate the effect of ethanol on cell proliferation and DNA synthesis [27,29]. A recent study demonstrated that EGF-like growth factors can reduce apoptosis and enhance cell proliferation caused by exposure to alcohol [30].…”
Section: Discussionmentioning
confidence: 99%
“…Etanolün insan hücre hatları canlılığı üzerindeki etkisi. *İstatistiksel olarak anlamlı farkı gösterir, p<0.05. , mouse hippocampal (HT22), Swiss 3T3 and human umbilical vein endothelium (HUVEC) and it has been demonstrated that the IC50 values of ethanol on the studied cells vary between 0.1% and 5% (v/v) (Yeo et al 2000;Clave et al, 2014;Casañas-Sánchez et al, 2016;Jamalzadeh et al, 2016). The mechanism of this cytotoxic effect of ethanol is explained by its property to increase the amount of reactive oxygen species (ROS), rate of apoptosis and to modulate the amount of many proteins, such as adenylate cyclase, protein kinase C, protein tyrosine kinases and phospholipase C and D (Mikami et al, 1997;Yeo et al, 2000;Clave et al, 2014;Casañas-Sánchez et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…*İstatistiksel olarak anlamlı farkı gösterir, p<0.05. , mouse hippocampal (HT22), Swiss 3T3 and human umbilical vein endothelium (HUVEC) and it has been demonstrated that the IC50 values of ethanol on the studied cells vary between 0.1% and 5% (v/v) (Yeo et al 2000;Clave et al, 2014;Casañas-Sánchez et al, 2016;Jamalzadeh et al, 2016). The mechanism of this cytotoxic effect of ethanol is explained by its property to increase the amount of reactive oxygen species (ROS), rate of apoptosis and to modulate the amount of many proteins, such as adenylate cyclase, protein kinase C, protein tyrosine kinases and phospholipase C and D (Mikami et al, 1997;Yeo et al, 2000;Clave et al, 2014;Casañas-Sánchez et al, 2016). There are various report about the cytotoxic effect of DMSO on various cell lines, such as colon cancer (CaCo-2), retinal ganglion (RGC), astrocyte, human leukemic (THP1, U937, Jurkat, Molt-4) cell lines and it is reported that the IC50 values of DMSO on these cell lines vary between 0.5% to 3% (v/v) (Da Violante et al, 2002;Galvao et al, 2014;Yuan et al, 2014;Hajighasemi and Tajik, 2017;Singh et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation